Construction Site Management and Labor Productivity Improvement : How to Improve the Bottom Line and Shorten the Project Schedule. - Thomas, H. Randolph, 1945- (ASCE Press Ser., 2017)
Thomas and Ellis provide detailed, straightforward management practices to improve construction site activity and reduce losses in labor productivity from the most common site challenges.